Genotoxic effect of an organophosphorus compound (Phosphamidon) on the Bone Marrow of Albino Rats - Kuwar, RB; Jha, CB; Saxena, AK; Bhattacharya, S (Journal of Institute of Medicine Nepal, 2009)
Introduction: The present study shows the genotoxic effect of phosphamidon on bone marrow of albino rats and this study was conducted in the cytogenetic laboratory, at B.P. Koirala Institute of Health Sciences, Dharan, Nepal. Materials and Methods: Rats were treated by drinking water containing 35 parts per million and 50 parts per million concentration of phosphamidon(an organophosphorus compound) for 30 days. After 30 days, they were sacrificed. The femur was dissected out and the bone marrow from femur was aspirated. The bone marrow was immediately processed and then slides were prepared and then observed in 100X oil immersion microscopy for chromosomal aberrations. Results: Different type of Chromosomal aberrations were observed in both experimental groups like gaps, accentric fragments, containing single and double minutes, fragmentation, centromeric breakage and premature condensation of chromosomes. Conclusion: Phosphamidon has profound genotoxic effect in experimental albino rats. Key words: Phosphamidon, Bone marrow, chromosomal aberration, genotoxicity, chromosome The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 34-36